Między islamizacją a okcydentalizacją. Wpływ procesów globalizacyjnych na strukturę etniczno kulturową krajów regionu Zatoki Perskiej - Kulupa, Julianna; Czechanowski, Przemysław (Studia Azjatystyczne, 2016)
The countries situated on the west coast of the Persian Gulf base their economies on the export of oil, which inevitably opened them up to processes inherent in global relations. This led the Arab states of the Persian Gulf in the last 30 years of the 20th century to enrichment and increased their economic significance. Over time, growing fluctuations in oil prices enforced not only a process of diversification into their economic model through an extension of the service sector, but also brought in a work force from other countries. This changed ethnic relations in the region. New inhabitants, who are mainly from western countries, have brought with them not only their cultural values, but their education system as well. Gulf Cooperation Council countries have recognized mass immigration as temporary phenomenon. They have plans to educate the local work force and end migration, based on the experience of outside models. These plans have gone wrong owing to cultural limitations. Modern education has had an influence on the attitudes and expectations of the local youth, pushing them in the direction of westernisation. In response to this process, its opponents have supported Islamic projects. Persian Gulf countries have modernised their economies, but at the cost of globalization and the disintegration of the local society. The positive aspect of this process, which can be a good example for other countries in the Middle East, has been the creation of the nation.